TECHNOLOGICAL FEATURES OF THE PRODUCTION OF CASTINGS OF ALUMINUM ALLOY BY CASTING INTO THE CHILL MOLD - M. A. Sadokha; A. P. Melnikov; A. S. Mironov; I. V. Rak (Литьë и металлургия)
The technological features of the production of castings of aluminum alloys by chill casting are showed. The most important features of chill casting are considered.